Genius Ideas and Genius Mistakes: A Clinical Approach - Mikhail Reshetnikov (Issues and Development in Health Research Vol. 7, 2021)
In this paper, a number of outdated but still prevailing medical doctrines are critically reviewed, in particular, Hippocrates’s hypothesis of the brain as a repository of all mental processes; I.M. Sechenov’s hypothesis of the psyche as a derivate of the brain reflexes; I.P. Pavlov’s hypothesis of the higher nervous activity as an equivalent of the psyche. Currently, therapy of mental disorders is conducted mostly by means of psychopharmacology, which targets the exchange of neurotransmitters in the synaptic cleft and thus is supposed to influence the psyche. In his research, the author refers to studies of feral children, studies of memory and subliminal perception, discovery of mirror neurons and contemporary views of the academic science on information. The author proves the non-materiality of the psyche and the role of the brain as a biological interface between the ideal and the real. The new approach would require changing the traditional paradigm as well as all our approaches to studying the psyche and treating mental disorders. What remains to be said is of so novel and unheard of a character that I not only fear injury to myself from the envy of a few, but I tremble lest I have mankind at large for my enemies, so much to wont and custom that become as another nature, and doctrine once sown that hath struck deep root, and respect for antiquity, influence all men. William Harvey. In “On the Motion of the Heart and Blood” (1628).